The Ijtima Ulama on Voter Preferences in the 2024 Elections in Indonesia - Rabbani, Ammar; Gesit Yudha; Tin Amalia Fitri (Universitas Islam Negeri Raden Intan Lampung, 2025)
The 2024 Simultaneous Elections mark a significant dynamic in Indonesian politics, particularly regarding the strengthening role of religious authorities in shaping Muslim voter preferences. In several regions, including West Bogor District, the direction of support from Islamic scholars through the Ijtima Ulama forum has implications for the formation of diverse community political preferences. This study aims to analyze the influence of the Ijtima Ulama on voter preferences in the 2024 Simultaneous Elections in Indonesia. The study used a mixed methods design with a sequential exploratory approach, qualitative research followed by quantitative research. Qualitative data were obtained through in-depth interviews and analyzed through data condensation, data presentation, and validity verification. Quantitative data were collected through questionnaires from 114 respondents and analyzed using simple linear regression, t-test, and coefficient of determination (R²). The results showed that the Ijtima Ulama had a significant effect on voter preferences (t count = 16.614 > t table = 1.981; sig. 0.000 < 0.05) with a contribution of 70.9%. This finding aligns with the theory of social influence, which emphasizes the role of moral authority through mechanisms of compliance, identification, and internalization. From an Islamic perspective, this influence is reinforced by the scholarly authority of ulama, the principle of taqlid (following), and an orientation toward the welfare of the people, allowing the Ijtima Ulama to serve as both a moral and socio-political reference point in shaping voter preferences.